2020
DOI: 10.3390/rel11090466
|View full text |Cite
|
Sign up to set email alerts
|

A Spirituality Mind-Body Wellness Center in a University Setting; A Pilot Service Assessment Study

Abstract: Increasing rates of mental illness among college students over the past 10 years suggest a collective deficit in meaning and purpose unattended to by many university campuses. Psychopathology among young adult college students is associated with developmental tasks such as spiritual individuation, suggesting that interventions aimed at spiritual wellbeing may support the stated need for comprehensive mental health services. The aim of this pilot service assessment study is to investigate the feasibility, accep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Spiritual-mind-body wellness interventions may be a targeted prevention approach to address mental health needs for undergraduate students ( Adams et al, 2000 ; Ewing et al, 2007 ), and may support the development of spirituality in emerging adulthood ( Scalora et al, 2020 ), which has been shown to protect against depression ( Bonelli et al, 2012 ; Miller, 2013a ). Such SMB wellness interventions may provide resources and spiritual community – an antidote to loneliness and an essential catalyst for individual inner growth – to attend ultimately to the developmental task of spiritual individuation ( Adler, 1938 ; Rodríguez-Romero et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Spiritual-mind-body wellness interventions may be a targeted prevention approach to address mental health needs for undergraduate students ( Adams et al, 2000 ; Ewing et al, 2007 ), and may support the development of spirituality in emerging adulthood ( Scalora et al, 2020 ), which has been shown to protect against depression ( Bonelli et al, 2012 ; Miller, 2013a ). Such SMB wellness interventions may provide resources and spiritual community – an antidote to loneliness and an essential catalyst for individual inner growth – to attend ultimately to the developmental task of spiritual individuation ( Adler, 1938 ; Rodríguez-Romero et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Scalora et al. (2020) measured changes in six of these domains across pre/posttests using psychometric assessments germane to each domain. Furthermore, the SMB program integrated many Buddhist informed or Buddhist converging workshops (i.e., mindfulness skills, yoga, discovering no‐self, and contemplative practices).…”
Section: Spiritual But Not Religiousmentioning
confidence: 99%
“…Upon examining the relevant literature, there do not seem to be any empirical studies linking specific spiritual theoretical orientations to SBNR clients. However, in a pilot service assessment study, Scalora et al (2020) tested a spiritual mind-body (SMB) program on 141 graduate students in order to measure the program's effectiveness across several different wellness domains. The 8-week SMB program was designed to attenuate depressive, anxious, and posttraumatic stress symptoms and increase psychological flexibility, personal spirituality, and mindfulness.…”
Section: Theoretical Orientation Gaps and Alignment With The Sbnrmentioning
confidence: 99%
See 1 more Smart Citation